Elasto - plastic analysis of anisotropic hardening materials by finite element method - Hien, Tran Duong (Vietnam Journal of Mechanics, 1985)
An elasto- plastic analysis for general three dimes10nal problems using a finite element model is presented. The analysis is based on Hill’s yield criterion which included anisotropic materials displaying kinematic - isotropic hardening. The validity and practical applicability of the algorithm are illustrated by a number of numerical examples, calculated by a computer program written in fortran.